2021
DOI: 10.1021/acs.jafc.1c03449
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Improves Hyperuricemia-Induced Chronic Kidney Disease via Regulating Gut Microbiota-Mediated Tryptophan Metabolism and Aryl Hydrocarbon Receptor Activation

Abstract: The intestinal flora serves a critical role in the development of hyperuricemia-induced chronic kidney disease (CKD). We previously found that natural flavonol fisetin exhibited nephroprotective effects in hyperuricemic mice. However, the mechanism remains largely unknown. To investigate the underlying mechanism of fisetin, mice were fed with potassium oxonate and adenine to introduce hyperuricemia-induced CKD. Fisetin improved kidney function, ameliorated renal fibrosis, and restored enteric dysbacteriosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…In addition, studies also found that some chemical drugs also modulate Trp metabolism in gut microbiota, such that Fisetin can modulate the gut microbiota-mediated Trp metabolism [ 57 ]. Rifaximin affected Trp synthesis in the gut microbiota [ 58 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies also found that some chemical drugs also modulate Trp metabolism in gut microbiota, such that Fisetin can modulate the gut microbiota-mediated Trp metabolism [ 57 ]. Rifaximin affected Trp synthesis in the gut microbiota [ 58 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
“…Fructooligosaccharides protect against OVA-induced food allergy in mice by regulating the Th17/Treg cell balance using Trp metabolites [ 46 ]. Fisetin could improve hyperuricemia-induced chronic kidney disease via regulating the gut microbiota-mediated Trp metabolism [ 57 ]. Interestingly, honeybee gut lactobacillus modulates host learning and memory behaviors via regulating the Trp metabolism [ 175 ].…”
Section: Potential Application Of Gut Microbiota-derived Trp Metaboli...mentioning
confidence: 99%
“…Wang et al identified novel poricoic acids from Poria cocos and found that they attenuated renal fibrosis through the modulation of AHR signaling pathway in TGF-ÎČ1-induced cultured human kidney proximal tubular epithelial cells and mice with unilateral ureteral obstruction ( Wang M. et al, 2020 ). Fisetin, a bioactive flavonol, was reported to improve hyperuricemia-induced CKD via regulating gut microbiota-mediated tryptophan metabolism and AHR activation ( Ren et al, 2021 ). In our study, JPYSF was found to suppress the activation of AHR signaling in the kidney of CKD rat.…”
Section: Discussionmentioning
confidence: 99%
“…Among uremic toxins, those derived from tryptophan metabolism are particularly of importance because they are associated with cardiovascular toxicity and are the ligands of the aryl hydrocarbon receptor (AHR) ( Brito et al, 2017 ). Emerging evidence implicated that the AHR signaling pathway was activated both in CKD patients and in animal models of CKD ( Dou et al, 2018 ; Ren et al, 2021 ). The AHR is a ligand-activated nuclear transcription factor that belongs to the basic helix-loop-helix protein superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…Additional putative mechanisms of action of fisetin in prostate cancer include microtubule stabilization (10 ”M) [58], inhibition of epithelial-to-mesenchymal transition (60 ”M) via inhibition of YB-1 [53], TRAILmediated augmentation of apoptosis (50 ”M) [59], inhibition of cell cycle (1-50 ”M) [60][61][62], induction of autophagic cell death via mTOR suppression [63], and inactivation of the JNK and PI3K/Akt signaling pathways [64]. Fisetin may also favorably modulate gut microbiota [65], which is possibly involved in prostate cancer etiopathogenesis [66].…”
Section: Fisetin Preclinical Studiesmentioning
confidence: 99%